Anthology fever: Latin American narrative in transition to the 21st century (Revista de Crítica Literaria Latinoamericana, 2012)
The emergence of groups and the publication of many anthologies was a common phenomenon during the last fifteen years. These publications had a great influence on the promotion of the new narrators in Latin America, and have received a considerable attention of critics and publishers, who saw in some of those writers the young talents that they could support. Here I review the phenomenon considering the anthology Novísimos narradores (1980), by Ángel Rama, as a prelude to the two main sections. First, the Mexican group “Crack” and its derivation into “from the boom to the boomerang” –with the intervention of Carlos Fuentes–, as well as the anthology McOndo. In the second part, the platforms of the subsequent compilations of new Spanish-American narrators, in the frame of Lipovetsky's theory about neoindividualism in the postmodern age.
Keywords: anthologies; Crack; McOndo; boomerang; neoindividualism; Lipovetsky